A review of the genus Amida Lewis (Coccinellidae: Ortaliini) from China - Wei, Xue-Yuan; Lin, Li; Chen, Lin; Yang, Xiao-Jun; Wang, Xing-Min (Zootaxa, 2024)
A review of the genus Amida Lewis, 1986 from China is presented. Thirteen species are recorded in total, including four new species, Amida sagittata Wei et Wang, sp. nov., Amida longifolia Wei et Wang, sp. nov., Amida motuensis Wei et Wang, sp. nov. and Amida nanlingiensis Wei et Wang, sp. nov., and two new recorded species from China: Amida nguyent Hoàng, 1983 and Amida mirifica Hoàng, 1983. Descriptions, re-descriptions and illustrations of all species are provided. A distribution map and an identification key are also given.